New tools to help boost your prevention impact. (2nd May 2019) - Waterall, Jamie
Abstract : Public Health England has launched a series of new e-learning tools to enhance health and care professionals' knowledge and skills. Professor Jamie Waterall discusses how these will address key public health issues and enhance approaches to preventing illness